Carotid Artery Dissection Causing an Isolated Hypoglossal Nerve Palsy - Ali, Muzzammil; Sardana, Yatin (Archives of Clinical and Medical Case Reports, 2018)
Carotid Artery Dissection (CAD) typically presents with an acute onset of neck pain and headache. It can occur spontaneously or secondary to neck trauma. Neck trauma can be major following a road traffic accident or assault, or can be minor, for example, through coughing, sneezing or hiccups. There is also a postulated link between CAD and upper respiratory tract infections. Here we describe an unusual case of CAD presenting as a hypoglossal nerve palsy which was preceded by a coryzal illness. It highlights the importance of maintaining a high index of suspicion in patients with acute focal neurology. The early diagnosis and management of CAD helps to prevent complications such as ischemic stroke or loss of vision.